What Now = Et maintenant - Pécoil, Vincent; Robecchi, Michele; Teerlinck, Hilde; CRAC Alsace, Altkirch (Altkirch : CRAC (Centre Rhenan d'Art Contemporain) Alsace Altkirch, 2006)
Collins, Phil; Deller, Jeremy; Kay, Emma; King, Scott; Locke, Hew; Petersen, Vinca; Saville, Peter; Turk, Gavin.
Engels
Frans
Publicatie n.a.v. de tentoonstelling "What now / Et maintenant" in het CRAC Alsace te Altkirch, 02.12.2005 - 19.02.2006
boek